1999
DOI: 10.1002/(sici)1096-8628(19991119)87:2<183::aid-ajmg11>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal structure of the sella turcica in Down syndrome

Abstract: The purpose of this study was to analyze the shape of the sella turcica in a group of patients with Down syndrome and compare the findings with those made earlier in human fetuses with Down syndrome. Profile radiographs from 78 patients (age 4 months to 50 3/12 years) were analyzed. A tracing was made of each sella turcica, and the shape was compared with that of a normal sella, including the normal growth pattern from childhood to adulthood. Sella turcica structure could be classified into three morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 20 publications
2
61
0
3
Order By: Relevance
“…Sella turcica dimensions reported by many researchers [11,15] are based on Caucasian populations and the data were mostly obtained from skull radiographs. Based on our investigation, it was observed that, this is the first time the sella turcica was investigated on computed tomography in the indigenous population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sella turcica dimensions reported by many researchers [11,15] are based on Caucasian populations and the data were mostly obtained from skull radiographs. Based on our investigation, it was observed that, this is the first time the sella turcica was investigated on computed tomography in the indigenous population.…”
Section: Discussionmentioning
confidence: 99%
“…The sella turcica is usually demarcated by a dense, thin white line in lateral radiographs. It is sometimes more important to recognize this feature than to estimate the size of the fossa [11].…”
Section: Introductionmentioning
confidence: 99%
“…Agenesis of all third molars was seen in 52% of our sample, similar to the 55% reported by Shapira et al 19 Because of the frequent agenesis of all third molars in our sample, we explored whether this occurrence was associated with any specific craniofacial features. Russel and Kjaer 41 hypothesized that an association in DS between the sella turcica structure and the innervations determined occurrence of tooth agenesis due to the proximity of sella to the trigeminal ganglion. In our cephalometric analysis, specific measurements (pituitary fossa diameter, sella turcica elevation from FHP, posterior maxillary vertical height, and the vertical distance of sella from the pterygomaxillary fissure) were included to explore whether the sella and vertical growth of the infrasellar region were differentially affected in individuals with DS having maxillary hypodontia and agenesis of all third molars, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can also occur in some syndromes and craniofacial abnormalities that affect the craniofacial region such as primary hypopituitarism, Williams syndrome, growth hormone deficiency, Cushing's syndrome, lumbosacral myelomeningocele, the presence of intrasellar adenomas, empty sella syndrome, and Rathke's cleft cysts and aneurysms [5,8,15,31,43]. By means of MRI, Baleriaux et al [9] concluded that macroadenomas, meningiomas, craniopharyngiomas, and cysts are more probable causes of deformation of the neighboring bony structures.…”
Section: Introductionmentioning
confidence: 99%